Annual reproductive cycle of male rohu, Labeo rohita (Ham.), in Tarai region of Uttaranchal - Kumar, Anup; Singh, I J; Ram, R N (Indian Journal of Fisheries, 2011)
Testicular development of Labeo rohita under ambient environmental conditions in Tarai region of Uttaranchal was associated with increasing day-length and temperature, whereas testicular maturity and spermiogenesis during spawning phase seem to be correlated with the lowering of water temperature, attributable to rainfall. The primary spermatogonial cells and spermatocytes, a few lobules with spermatozoa and spermatids were observed in preparatory phase. The peak of spermatogenesis having active interstitial Leydig cells was recorded during pre-spawning phase. During spawning phase, most of the testicular lobules were packed with sperm masses alongwith a few secondary spermatocytes and spermatids. Decreased interlobular space with some inactive interstitial cells was noticed during post-spawning phase. The histological changes in liver showing augmented biosynthetic activities corresponded with testicular growth and maturation and changes in hepatopancreatic cells were suggestive of energy mobilization